Gnotobiotic system for selecting microorganisms with biocontrol potential against Fusarium oxysporum f. sp. physali - Garcia, Diana; Dávila, Lizeth Lorena; González, Adriana; Caro, Alejandro; Cotes, Alba Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The cape gooseberry (Physalis peruviana) is a Solanaceae species with enormous economic importance in Colombia; it is the second most exported fruit, after bananas. Vascular wilt caused by Fusarium oxysporum f. sp. physali (Fox) is the most limiting factor of this crop, with losses of up to 80% of production. Biological control is a promising alternative for controlling this pathogen. Bacteria and fungi, originally isolated from potentially suppressive soils of cape gooseberry crops in Nariño, Colombia with different management (organic and conventional), were evaluated as biocontrol agents of Fox using a gnotobiotic model (seedlings cultured under axenic conditions with defined microbial strains). Of the 64 isolated microorganisms, 37.5% (15 bacteria and 9 fungi) were discarded because of toxicological risks and an unknow potential biological control. The remaining 62.5% of the microorganisms, 14 bacteria and 26 fungi, were evaluated to assess their potential as biological control agents against Fox. The gnotobiotic model system evaluated the protection and plant growth promotion characteristics. Response variables were used to group the microorganism using a principal component analysis (PCA), and five clusters were obtained. Cluster number four concentrated the 10 microorganisms (three bacteria and seven fungi) with the highest protection values against Fox, with a positive effect on growth. The isolates were identified as two Bacillus subtilis strains, Rhodococcus sp., Podospora setosa, Debaryomyces vindobonensis, Plectosphaerella plurivora, Acinetobacter rhizosphaerae, Umbelopsis sp. and two strains of Trichoderma koningiopsis. The gnobiotic system offered clear advantages for evaluating and selecting microorganisms with a biological control potential against Fusarium oxysporum f. sp. physalis.